2016
DOI: 10.1007/s10882-016-9494-0
|View full text |Cite
|
Sign up to set email alerts
|

Don’t Assume Deaf Students are Visual Learners

Abstract: In the education of deaf learners, from primary school to postsecondary settings, it frequently is suggested that deaf students are visual learners. That assumption appears to be based on the visual nature of signed languages—used by some but not all deaf individuals—and the fact that with greater hearing losses, deaf students will rely relatively more on vision than audition. However, the questions of whether individuals with hearing loss are more likely to be visual learners than verbal learners or more like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 43 publications
2
19
0
5
Order By: Relevance
“…Recent research (see Archbold, 2015;Harris, 2016, for reviews) has demonstrated significant benefits of cochlear implantation to young deaf children's speech and language, school achievement, and social-emotional functioning (the last usually according to parent reports). Benefits to achievement, however, largely have been found to disappear by high school and college age (Geers & Hayes, 2011;Geers et al, 2008;Harris & Terlektsi, 2010;Marschark, Shaver et al, 2015), at which time there also appears to be little if any difference between deaf individuals with and without CIs across a variety of cognitive domains (Figueras et al, 2008;Marschark, Spencer et al, 2015;Marschark, Paivio et al, 2016). As noted earlier, this finding has been suggested to reflect greater difficulty and differing goals of reading at the high school level (Archbold, 2015), the need for longer term interventions following cochlear implantation (Nittrouer & Caldwell-Tarr, 2016) or the involvement of alternative cognitive and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research (see Archbold, 2015;Harris, 2016, for reviews) has demonstrated significant benefits of cochlear implantation to young deaf children's speech and language, school achievement, and social-emotional functioning (the last usually according to parent reports). Benefits to achievement, however, largely have been found to disappear by high school and college age (Geers & Hayes, 2011;Geers et al, 2008;Harris & Terlektsi, 2010;Marschark, Shaver et al, 2015), at which time there also appears to be little if any difference between deaf individuals with and without CIs across a variety of cognitive domains (Figueras et al, 2008;Marschark, Spencer et al, 2015;Marschark, Paivio et al, 2016). As noted earlier, this finding has been suggested to reflect greater difficulty and differing goals of reading at the high school level (Archbold, 2015), the need for longer term interventions following cochlear implantation (Nittrouer & Caldwell-Tarr, 2016) or the involvement of alternative cognitive and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…There is a diversity of learning styles among normal students, they could be verbal, visual or a different type of learners. Therefore, it's crucial to include all possible learning styles for deaf students' e-learning techniques [33,34].…”
Section: Personal Skills-mentioning
confidence: 99%
“…In recent times, information technology and internet network are now being employed in educating deaf children [24,25], and this allows sign language to be combined with oral language [26]. Other learning models make use of written illustrations that are very easy to understand accompanied by visualization of nouns, verbs, adverbs, and other figures [27].…”
Section: Introductionmentioning
confidence: 99%